Representing the Mother's Role in the YouTube Ad: A Roland Barthes Semiotic Analysis of 'Mother's Amazing Hands’ - Muhamad Yusuf Alfauzi; Oktaviana Purnamasari (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
In advertising, females are frequently positioned as the center of attention to establish product image through culturally recognized signs and symbols. Advertisements transcend their promotional function, acting as media that both reflect and influence societal perceptions, including gender roles within daily life. This is exemplified in the Vicks VapoRub advertisement titled